The Old Phase of Javanese Villages as an Early Form of Participatory Democratic Governance in Indonesia - Kusumastuti Kusumastuti (The Institute for Research and Community Services, Institut Teknologi Bandung, 2017)
Abstract. Indonesia has experienced seven developmental phases of the social system (ideology), i.e. (1) the old phase of Javanese villages (809 AD); (2) the kingdom era (1044-1886); (3) the colonial Dutch East Indies (1853 AD); (4) the Japanese occupation (1942-1945); (5) the settling period from 1945 to 1965; (6) the New Order (1965-1998); and (7) The Reform Era. This ideology affects the development system, which in turn affect the relationship between government and people, such as on the position, rights, and roles of the people in influencing and determining the direction, content and development priorities. Meanwhile, democracy as a political system will affect the development system. Likewise, the decision-making system for developments is strongly influenced by the political system. This paper aims to retrace the democracy in the social system of the